Tools for Computational Finance - Seydel, Rüdiger U. (Universitext, 2009)
This book is very easy to read and one can gain a quick snapshot of computational issues arising in financial mathematics. Researchers or students of the mathematical sciences with an interest in finance will find this book a very helpful and gentle guide to the world of financial engineering. SIAM review (46, 2004). The fourth edition is thoroughly revised and extended. Major revisions concern topics like calibration, Monte Carlo Methods, American options, exotic options and Algorithms for Bermuda Options. New figures, more exercises, more background material make this guide to the world of financial engineering a real must-to-have for everyone working in FE.